Sociodemographic markers of high Sensory Processing Sensitivity: a descriptive study - Morales-Botello, María-Luz; Betancort, Moisés; Pérez-Chacón, Manuela; Rodríguez-Jiménez, Rosa-María; Chacón, Antonio (Frontiers in Psychology, 2025)
IntroductionSensory Processing Sensitivity (SPS) represents a personality trait characterised by heightened responsiveness to environmental stimuli, which can lead to both beneficial and adverse outcomes. Despite the exponential growth in knowledge about SPS in recent years, sociodemographic dimension related to this trait remains under-researched. The primary aim of this study was to analyse and provide deeper insights into the sociodemographic characteristics that may distinguish highly sensitive individuals. The present study was approached from the perspective of different sensitivity levels (low-SPS, medium-SPS and high-SPS).MethodsTo examine the sociodemographic expression of SPS, we pursued two main objectives. Firstly, by logistic regression analysis, we investigated the sociodemographic characteristics that predict high-SPS. Secondly, by analysis of variance and post hoc analysis, we investigated whether the relationship between SPS and sociodemographic variables depended on the SPS level. We conducted these analyses based on a large sample from the general population (9,447 participants were initially considered).ResultsThe logistic regression analysis identified significant predictors of high sensitivity, spanning demographic, social, and wellbeing-related variables. Specifically, gender, age, civil status, number of children and type of residence as demographic variables; number of social groups and satisfaction with partner as social variables; and practise of body awareness activities as a wellbeing variable significantly predicted high-SPS. Moreover, analysis of variance and post hoc analysis, evidenced that unlike low-SPS and medium-SPS, high-SPS (SPS trait) was relatively stable with respect to sociodemographic changes.DiscussionWe discuss our findings within the context of SPS, personality traits, and their practical implications for clinical, educational, and occupational settings. We hope that this work will contribute to identifying those who may need greater support in developing their wellbeing.